2023
DOI: 10.1101/gr.277483.122
|View full text |Cite
|
Sign up to set email alerts
|

Motif conservation, stability, and host gene expression are the main drivers of snoRNA expression across vertebrates

Abstract: Small nucleolar RNAs (snoRNAs) are structured noncoding RNAs present in multiple copies within eukaryotic genomes. SnoRNAs guide chemical modifications on their target RNA and regulate processes like ribosome assembly and splicing. Most human snoRNAs are embedded within host gene introns, the remainder being independently expressed from intergenic regions. We recently characterized the abundance of snoRNAs and their host gene across several healthy human tissues and found that the level of most snoRNAs does no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Instead they could be classified as pseudogene (Figure 3A). This is supported by the fact that host gene expression is a positive indicator of intronic snoRNA expression, which is the opposite in the case of 34 out of the 37 non expressed snoRNAs whose respective host gene is expressed (50). Finally, our de novo search for non-annotated snoRNAs yielded only one hit, snoCD45, but we cannot exclude that future tools or different parameters could reveal new C/D box snoRNAs in D. melanogaster.…”
Section: Discussionmentioning
confidence: 91%
“…Instead they could be classified as pseudogene (Figure 3A). This is supported by the fact that host gene expression is a positive indicator of intronic snoRNA expression, which is the opposite in the case of 34 out of the 37 non expressed snoRNAs whose respective host gene is expressed (50). Finally, our de novo search for non-annotated snoRNAs yielded only one hit, snoCD45, but we cannot exclude that future tools or different parameters could reveal new C/D box snoRNAs in D. melanogaster.…”
Section: Discussionmentioning
confidence: 91%
“…Much of the discrepancy in expression of snoRNAs and their host genes can be explained by known mechanisms of RNA regulation [ 48 ] including NMD [ 64 ], dual initiation promoters [ 56 ] and alternative processing of snoRNAs [ 65 ]. A recent computational study showed that motif conservation, overall snoRNA stability, formation of terminal stem and the host gene expression serve as main predictors of snoRNA expression [ 66 ]. Although it is evident that the genomic organization of a snoRNA dictates its maturation path, it remains unclear to what extent a snoRNA’s pathway to maturity influences its abundance and function.…”
Section: Genomic Loci and Organization Of Snornasmentioning
confidence: 99%